Improved Mathematics Learning Outcomes Through Problem Based Learning Models In Class VA SDN 01 Karangpandan - Diana Kusuma Sari (Universitas Sebelas Maret, 2022)
The background of this research is the low mathematics learning outcomes of VA class at SD Negeri 01 Karangpandan. The aim of this research is to improve the learning outcomes of VA grade students at SD Negeri 01 Karangpandan through the Problem Based Learning model. This research is a classroom action research carried out in two cycles, four stages in each cycle, with VA class subjects. Based on the results of the study it can be said that the application of the PBL model was able to improve the mathematics learning outcomes of VA class. Judging from the increase in the percentage of completeness and the average value of students in fractional material, from 25% completed in pre-cycle learning, 70% in cycle I and increased to 86% in cycle II. The average value of 60.52 in pre-cycle, 77.93 in cycle I and increased to 87.24 in cycle II. So it can be concluded that the application of the PBL learning model was able to improve the learning outcomes of VA class students in the Mathematics lesson on fraction material at SD Negeri 01 Karangpandan in the 2021/2022 academic year